Alex Tiong named UMP Sportsman of the Year - UMP, PNC (2018)
Alex Tiong Sie Hung, an undergraduate at Faculty of Civil Engineering & Earth Resources (FKASA) was named Sportsman of the Year by Universiti Malaysia Pahang (UMP) following his triumphant feats including gold medals won in the swimming event of SUKIPT and MASUM 2018.